Inovasi Penerjemahan Digital Berbasis Kecerdasan Buatan: Studi Komparatif antara ChatGPT, Google Translate, dan Penerjemah Manusia dalam Teks Sastra dan Ilmiah - Irma Rachmayanti; Mochamad Arifin Alatas; A. Samsul Ma'arif; Albaburrahim Albaburrahim; Sahrul Romadhon (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
This study is motivated by the fact that the development of artificial intelligence (AI) technology has revolutionized various fields, including the practice and teaching of translation. It examines digital translation innovations powered by AI through a comparative study of ChatGPT, Google Translate, and human translators in the context of literary and scientific texts. The research combines four previous research approaches using a mixed-methods design, involving analysis of translation students’ perceptions, quality assessment of Arabic literary text translations, linguistic evaluation of scientific texts, and expert assessments of classical Arabic poetry. The findings indicate that ChatGPT is preferred over Google Translate in literary translation, particularly for its fluency and contextual relevance, although it still lags behind human translators in terms of cultural accuracy. In scientific text translation, ChatGPT excels in terminological accuracy but lacks flexibility in syntactic structure. Meanwhile, in classical poetry translation, ChatGPT is considered capable of competing with human translators in terms of thematic clarity, creativity, and prosody, significantly outperforming Google Gemini. This study highlights the importance of collaborative utilization between AI and human translators to achieve accurate, contextual, and functional translations in education and language services in the digital age.Penelitian ini dilatarbelakangi adanya perkembangan teknologi kecerdasan buatan (AI) telah merevolusi berbagai bidang, termasuk praktik dan pembelajaran penerjemahan. Penelitian ini mengkaji inovasi penerjemahan digital berbasis kecerdasan buatan (AI) melalui studi komparatif antara ChatGPT, Google Translate, dan penerjemah manusia dalam konteks teks sastra dan ilmiah. Kajian ini memadukan empat pendekatan penelitian terdahulu dengan metode campuran (mixed methods), melibatkan analisis terhadap persepsi mahasiswa penerjemah, penilaian kualitas terjemahan teks sastra Arab, evaluasi linguistik terhadap teks ilmiah, serta penilaian ahli terhadap puisi Arab klasik. Hasil penelitian menunjukkan bahwa ChatGPT lebih disukai dibanding Google Translate dalam penerjemahan sastra, terutama karena kelancaran dan kontekstualitasnya, meskipun masih kalah dalam aspek akurasi budaya dibanding penerjemah manusia. Dalam penerjemahan teks ilmiah, ChatGPT unggul dalam keakuratan istilah tetapi kurang fleksibel dalam struktur sintaksis. Sementara itu, pada puisi klasik, ChatGPT dinilai mampu bersaing dengan penerjemah manusia dalam aspek kejelasan tema, kreativitas, dan prosodi, jauh melampaui performa Google Gemini. Penelitian ini menegaskan pentingnya pemanfaatan kolaboratif antara AI dan penerjemah manusia untuk mencapai hasil terjemahan yang akurat, kontekstual, dan berdaya guna dalam pembelajaran serta layanan kebahasaan era digital.